Sinkronisasi Global: Taktik Koordinasi Waktu Adaptif untuk Tim IT Agile Virtual - Tsani, Muhammad Rizqi; Sudiarno, Adithya (SOTVI - Society of Visual Informatics, 2025)
The global adoption of Agile methodologies in virtual IT teams presents a fundamental conflict with the principle of face-to-face communication, with temporal distance posing a primary operational barrier. This research identifies and analyzes the adaptive time-coordination tactics that globally dispersed Agile teams employ to overcome this challenge. The study utilized a qualitative, phenomenological approach, conducting semi-structured interviews with practitioners from teams spanning up to a 15-hour time zone difference. The analysis reveals that effective teams do not force full-day synchronization but instead strategically leverage a limited synchronous ‘overlap window’ for high-bandwidth collaboration. Complementing this, teams implement a disciplined ‘asynchronous handoff’ to create a continuous, 24-hour workflow, transforming temporal separation into a strategic advantage. Key findings also show that teams pragmatically reconfigure Agile ceremonies, often replacing daily stand-ups with asynchronous updates, and foster individual autonomy to maintain productivity. The study concludes that success in virtual Agile environments hinges on a flexible framework of emergent, context-aware tactics rather than rigid adherence to traditional practices. These insights provide actionable strategies for managers to enhance the temporal efficiency and coordination of virtual projects.